"When the Prescription Pad Is Not Enough": Attention-Deficit Hyperactivity Disorder Management 2.0. Issue 1 (February 2017) - Radesky, Jenny; Reddy, Arathi; Steiner, Naomi; Augustyn, Marilyn
Abstract : CASE: Jose is a 13-year-old boy who presents to his primary care provider after struggling in school for many years. When he was in the first grade, he was diagnosed at a tertiary center with attention-deficit hyperactivity disorder. Multiple medication trials have produced few benefits and many side effects including poor sleep, morbid thoughts, lack of motivation, and, according to his parents, "he seemed like a robot." He comes now for his annual physical in April, and the parents tell you that the school is threatening that he be retained in the seventh grade. Parents are very adamant they do not want to try another medication. They have brought you their own and his advisor's Vanderbilt's, which each endorse 7 of 9 inattentive symptoms including trouble organizing, poor attention to detail, and easily distracted and forgetful in daily activities. His birth history and developmental history before beginning formal schooling are unremarkable. His first language was English whereas his parents speak Spanish to each other but not the children. He is healthy and without a history of head trauma, seizures, meningitis, or lead poisoning. An aunt has "learning problems." Jose's family lives in a crowded section of a large urban area. They share an apartment with another family, and both parents are employed full time with his father holding 2 full time jobs working double shifts. Their annual income is at the poverty line. There are 4 children in the family aged between 6 and 13 years. His school has been deemed a "recovery school" because of performing below standard on district-wide achievement tests. His classroom has 27 students, many of whom are English language learners, and he is not on an individualized education plan or 504 accommodations. The family is very concerned about the possibility of retention but have decided that "medicine does not help, " and they look to you for other recommendations. Where do you go next?